Human-Animal Relationships in Supported Housing: Animal Atmospheres for Mental Health Recovery - Friesinger, Jan Georg; Birkeland, Bente; Thorød, Anne Brita (Frontiers in Psychology, 2021)
Being in a relationship with an animal can promote the well-being of people. For many individuals, this usually takes place at home. This study reports about homes for people with mental health problems (with or without co-occurring substance use), who live in supported housing operated by public landlords, entailing tenancies that are usually stricter regarding their pet policies than ordinary homes. We thus addressed the following research questions through ethnographic fieldwork at seven distinct places: which types of human–animal relationships occur in supported housing, and how do they affect the tenants? We analyzed the collected data informed by the Grounded Theory approach and found three types of human–animal relationships within supported housing affecting the tenants differently, namely, “no animals,” “visiting animals,” and “shared/sole ownership of animals.” Animals in the buildings can stage atmospheres that promote solidarity and connectedness among people. In contrast, situations in which animals are forbidden can create emotional tensions between tenants and staff or landlords. When discussing fostering animal atmospheres and limits to keeping pets, we concluded that animals can contribute to the mental health recovery of tenants by creating acknowledgment and rootedness. Therefore, public housing services need to guarantee equal rights to the tenants as they do with every citizen, including the right to keep a pet.